Análisis, diagnóstico y perspectivas de la investigacion psicoeducacional en el Perú - Lazarte, Carmen (1991)
The article describes Psychoeducational research done in Peru, reviewing thesis, sorne memoires, research summaries and reports, congresses, catalogs, and diagnosis publications, as well as journals and sorne books. Psychoeducational research stages are described and theses, publications, and INIDE research reports are analyzed on the basis of a series of criteria. Finally, a diagnosis of the situation of psychoeducational research in Peru is delineated.